Examining the impacts of input factor application, production efficiency, and inefficiency model on maize yield: employing the stochastic frontier model in search of more efficient ways in managing maize farming - Muslim Salam; Ayu Anisa Amir; A Nixia Tenriawaru; Muhammad Hatta Jamil; Letty Fudjaja; Muhammad An-Nashrullah K Samma; Ahmad Imam Muslim; Hamed Noralla Bakheet Ali; Muhammad Ridwan (Environmental Research Communications)
Maize is a significant food crop in Indonesia’s agricultural development endeavors. In South Sulawesi Province, Bantaeng Regency is one of the regencies that developed corn farming with a large land area. This study aimed to examine the impact of input application on maize yield and assess the degree of efficiency and inefficiency in maize farming. The study was conducted in Bantaeng Regency, utilizing a sample size of 180 households engaged in maize farming as the primary data collection method. The data collected was analyzed using the Stochastic Frontier Cobb-Douglas Model, Technical Efficiency Analysis, Allocative Efficiency Analysis, Economic Efficiency Analysis, and Inefficiency Model. The findings indicated that the variables of land area, seed application, urea fertilizer, insecticide, and herbicide exhibited a significant positive impact on yields of maize. Conversely, the variable of NPK fertilizer had a significant negative impact. In the meantime, it is observed that the labor variable demonstrates a negative impact. The observed values in technical (0.544), allocative (1.840), and economic (1.001) suggest that maize cultivation has not attained technical, allocative, or economic efficiency. Meanwhile, it was also found that the variables significant positive to the technical inefficiency of maize farming are farming experience and education level. Therefore, in a short-term perspective, from a technical-managerial perspective, expanding the area of land under management, increasing the volume of seeds, urea fertilizer, insecticides, and herbicides to the optimum use is the right choice and an effective way for farmers to increase maize production. On the local government side, reviewing the price of certified seeds, subsidizing the price of maize seeds, ensuring the availability of urea and NPK fertilizers, insecticides, and herbicides, and intensifying extension activities and technical guidance on maize cultivation are alternative agricultural policies that the government can implement to support the efficiency and effectiveness of maize farming management.